Hepatitis B Virus (HBV) Genotype Mixtures, Viral Load, and Liver Damage in HBV Patients Co-infected With Human Immunodeficiency Virus - Jose-Abrego, Alexis; Roman, Sonia; Rebello Pinho, João Renato; de Castro, Vanessa Fusco Duarte; Panduro, Arturo (Frontiers in Microbiology, 2021)
Hepatitis B virus (HBV) co-infection is possible in patients who are positive for human immunodeficiency virus (HIV) since both share similar transmission routes. Furthermore, through the continuous risk of exposure, they potentially can be infected by mixtures of distinct HBV genotypes which can result in the presence of two or more genotypes in a single patient. This study aimed to specify the frequency of mixtures of HBV genotypes and their potential clinic importance in HIV-infected Mexican patients. HBV infection was assessed by serological testing and molecular diagnostics. HBV mixtures were detected by multiplex PCR and DNA sequencing. Liver fibrosis was evaluated using transitional elastography, the Aspartate aminotransferase to Platelets Ratio Index score, and Fibrosis-4 score. Among 228 HIV-infected patients, 67 were positive for HBsAg. In 25 HBV/HIV co-infected patients, 44 HBV genotypes were found: H (50.0%, 22/44), G (22.7%, 10/44), D (15.9%, 6/44), A (9.1%, 4/44) and F (2.3%, 1/44). Among these, 44.0% (11/25) were single genotype, 36.0% (9/25) were dual and 20.0% (5/25) were triple genotype. The most frequent dual combination was G/H (44.4%, 4/9), while triple-mixtures were H/G/D (60.0%, 3/5). The increase in the number of genotypes correlated positively with age (Spearman’s Rho= 0.53, p=0.0069) and negatively with platelet levels (Spearman’s Rho= 0.416, p=0.039). HBV viral load was higher in triply-infected than dually-infected (31623.0 IU/mL vs. 1479.0 IU/mL, p=0.029) patients. Triple-mixed infection was associated with significant liver fibrosis (OR=15.0 95%CI=1.29 - 174.38, p=0.027). In conclusion, infection with mixtures of HBV genotypes is frequent in HIV patients causing significant hepatic fibrosis related to high viral load, especially in triple genotype mixtures.